IMPLEMENTASI PROGRAM INDONESIA PINTAR SEKOLAH DASAR DI KECAMATAN TEMBALANG KOTA SEMARANG - Ega Aditya Alfa Riq; Tri Yuniningsih (Journal of Public Policy and Management Review, 2021)
Program Indonesia Pintar, hereinafter referred to as PIP or The Smart Indonesia Program, is government cash assistance provided to students whose parents are not and / or less able to pay for their education. The method used in this research is descriptive qualitative method. The purpose of this research is to see how the implementation of the Smart Indonesia Program (PIP) in Tembalang District Elementary Schools and to analyze the factors that influence its implementation by using the effectiveness of policy implementation through Riant Nugroho's "five right", namely: First policy accuracy, accuracy of implementation, Accuracy of targets, Accuracy of Environment and Accuracy of Process. The recommendation given is that the implementing agency should be more responsible for coordinating junior secondary schools and distribution banks, to be able to pay attention to the human resources involved in this program so that they are more adequate not only in quantity but also in quality, the implementing agency must be able to act firmly and strict on violations that occur, for the social environment, especially parents of the beneficiary Indonesia Pintar Program, must be better understood and comply with the provisions and technical programs of Indonesia Pintar